Regulation of Chemokine Production via Oxidative Pathway in HeLa Cells - Shinichiro Kina; Toshiyuki Nakasone; Hiroyuki Takemoto; Akira Matayoshi; Shoko Makishi; Nao Sunagawa; Feixin Liang; Thongsavanh Phonaphonh; Hajime Sunakawa (Mediators of Inflammation)
Inflammation is associated with disease progression and, by largely unknown mechanisms, has been said to drive oncogenesis. At inflamed sites, neutrophils deploy a potent antimicrobial arsenal that includes proteinases, antimicrobial peptides, and ROS. Reactive oxygen species (ROSs) induce chemokines. In the present study, the concentrations of IL-8 in culture supernatants of HeLa cells treated with ROS were determined by enzyme-linked immunosorbent assay. We used 𝑜-phenanthroline to deplete Fe2+ in order to investigate the mechanisms through which ROSs induce IL-8 secretion in our system. The iron chelator 𝑜-phenanthroline effectively inhibited H2O2-induced ERK2 activation. Enzyme-linked immunosorbent assays showed that IL-8 protein secretion was elevated in ROS-treated HeLa cells. When Fe2+ was removed from these cells, IL-8 secretion was inhibited. Collectively, these results indicate that Fe2+-mediated Erk pathway activation is an important signal transduction pathway in ROS-induced IL-8 secretion in epithelial cells.